PBP-A, a cyanobacterial dd-peptidase with high specificity for amidated muropeptides, exhibits pH-dependent promiscuous activity harmful to Escherichia coli - Gol Mohammad Dorrazehi; Matthias Winkle; Martin Desmet; Vincent Stroobant; Gamze Tanriver; Hervé Degand; Damien Evrard; Benoît Desguin; Pierre Morsomme; Jacob Biboy; Joe Gray; Karolina Mitusińska; et al. (Scientific Reports, 2024)
Abstract Penicillin binding proteins (PBPs) are involved in biosynthesis, remodeling and recycling of peptidoglycan (PG) in bacteria. PBP-A from Thermosynechococcus elongatus belongs to a cyanobacterial family of enzymes sharing close structural and phylogenetic proximity to class A β-lactamases. With the long-term aim of converting PBP-A into a β-lactamase by directed evolution, we simulated what may happen when an organism like Escherichia coli acquires such a new PBP and observed growth defect associated with the enzyme activity. To further explore the molecular origins of this harmful effect, we decided to characterize deeper the activity of PBP-A both in vitro and in vivo. We found that PBP-A is an enzyme endowed with dd-carboxypeptidase and dd-endopeptidase activities, featuring high specificity towards muropeptides amidated on the d-iso-glutamyl residue. We also show that a low promiscuous activity on non-amidated peptidoglycan deteriorates E. coli’s envelope, which is much higher under acidic conditions where substrate discrimination is mitigated. Besides expanding our knowledge of the biochemical activity of PBP-A, this work also highlights that promiscuity may depend on environmental conditions and how it may hinder rather than promote enzyme evolution in nature or in the laboratory.